2010
DOI: 10.2353/ajpath.2010.090883
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Mouse Model of Hyperglycemia and Retinal Neovascularization

Abstract: One of the limitations of research into diabetic retinopathy is the lack of suitable animal models. To study how the two important factors-hyperglycemia and vascular endothelial growth factor-interact in diabetic retinopathy, the Akimba mouse (Ins2 ). C57Bl/6 and the parental and Akimba mouse lines were characterized by biometric measurements, histology, immunohistochemistry, and Spectralis Heidelberg retinal angiography and optical coherence tomography. The Akimba line not only retained the characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
152
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(167 citation statements)
references
References 48 publications
9
152
0
6
Order By: Relevance
“…For this reason, the research group of Prof. Racokzy recently generated the Akimba (Ins2 Akita VEGF +/-) mouse model by crossing the diabetic Akita mouse line (Ins2 Akita ) with the Kimba mouse line (VEGF +/-) [119]. The Akita mouse is a naturally occurring insulin-dependent type 1 diabetes model [120,121].…”
Section: Transgenic Akimba Mouse Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the research group of Prof. Racokzy recently generated the Akimba (Ins2 Akita VEGF +/-) mouse model by crossing the diabetic Akita mouse line (Ins2 Akita ) with the Kimba mouse line (VEGF +/-) [119]. The Akita mouse is a naturally occurring insulin-dependent type 1 diabetes model [120,121].…”
Section: Transgenic Akimba Mouse Modelmentioning
confidence: 99%
“…The heterozygous Akita male mice develop features similar to early pathophysiological changes of diabetic complications, but fail to exhibit the advanced stage vascular dysfunctions. The non-diabetic Kimba (trVEGF029) mouse model, in which photoreceptors transiently overexpress hVEGF, is characterized by several early and advanced DR-associated vascular changes such as vascular permeability, capillary non-perfusion, microaneurysms and retinal neovascularization [119,[122][123][124][125][126][127]. It has been reported that the combination of high blood glucose levels and VEGF overexpression exacerbates the vascular complications in the Akimba mouse eye [119,127].…”
Section: Transgenic Akimba Mouse Modelmentioning
confidence: 99%
“…By P28, microvascular abnormalities and capillary dropout are observed and continue until 9 weeks of age, at which time pericyte loss is detected [123,124]. The Akimba mice are hyperglycemic and appear to have additive effects from both parental strains [125,126]. Akimba mice are characterized by pericyte and vessel loss and retinal neovascularization with diffuse vascular leakage that is observed in latestage DR [125,127].…”
Section: Mouse Genetic Models Of Drmentioning
confidence: 99%
“…Akimba mice are characterized by pericyte and vessel loss and retinal neovascularization with diffuse vascular leakage that is observed in latestage DR [125,127]. Additionally, the Akimba mouse exhibits leaky capillaries, tortuous vessels, and microaneurysm by 8 weeks [125]. Enhanced photoreceptor loss, reduction of retina thickness, increased persistence of edema, and retinal detachment are observed as the animal ages and disease progresses [125].…”
Section: Mouse Genetic Models Of Drmentioning
confidence: 99%
See 1 more Smart Citation